You say tomato? Collaborative remembering leads to more false memories for intimate couples than for strangers - French, Lauren; Garry, Maryanne; Mori, Kazuo (Memory (Hove), 2008)
Research on memory conformity shows that collaborative remembering-typically in the form of discussion-can influence people's memories. One question that remains is whether it matters with whom we discuss our memories. To address this question we compared people's memories for an event after they discussed that event with either their romantic partner or a stranger. Pairs of subjects watched slightly different versions of a movie, and then discussed some details from the movie, but not others. Subjects were better at remembering non-discussed details than discussed details: when remembering discussed details they incorrectly reported information from their partner's version instead of their own. In addition, subjects who discussed the event with their romantic partner (rather than with a stranger) were even more likely to report false memories. We discuss our findings in relation to other research on memory conformity, social influences on false memories, and memory systems within romantic relationships.